Evaluation of Genetic Diversity and Genetic Distance Between Twelve Chinese Indigenous Chicken Breeds Based on Microsatellite Markers - Ya-Bo, Yu; Jin-Yu, Wang; Mekki, D.M.; Qing-Ping, Tang; Hui-Fang, Li; Rong, Gu; Qing-Lian, Ge; Wen-Qi, Zhu; Kuan-Wei, Chen (International Journal of Poultry Science, 2006)
A total of 720 individuals of 12 indigenous chicken populations, geographically localized in Southern China were genotyped for 30 microsatellite markers in polymerase chain reaction (PCR) to evaluate the genetic variation and genetic distance between populations. All microsatellites were found to be polymorphic. Heterozygosity was calculated to determine the genetic variation. Of the 30 microsatellite loci, number of alleles per locus (Na) and effective number of alleles per locus (Ne) ranged from 4 to 11 and 2.157 to 8.019, respectively. The average expected heterozygosity (HE) was 0.669, while the average observed heterozygosity (HO) was 0.764. The polymorphism information content (PIC) has values between 0.560 and 0.641. Using Nei`s standard distance, genetic distance (DA) calculated ranged between 0.088 (Guanxi Sanhuang vs. Nandan Yao) and 0.495 (Huiyang Beard vs. Zhangzhou Game). The topology of phylogenetic trees constructed showed general patterns of relationship and genetic differentiation among the indigenous populations studied, however, both trees from Neighbor-Joining method and Unweighted Pair Group method showed a similar topology. The results provided evidence of the applicability of microsatellite to determining the genetic relatedness among different Chinese indigenous chicken populations and evaluating of genetic variations.